Monitoring termite population at rubber plantation using termite baiting system / Noor Lailatul Shuhada Hamzah - Hamzah, Noor Lailatul Shuhada (Faculty of Plantation and Agrotechnology, 2018)
Hevea bransiliensis was originally a native tree from Amazon. In early 20th century, it was introduced in Africa. The termite species, Coptotermes curvignathus began to attack the rubber plant from the roots of dead wood and the base around the stem of rubber. The main objective of the study is to identify and investigate the number of termites around rubber crop by using Termite Baiting System. Rotten wooden stick and cardboard in the PVC plastic pipe were used as their baits to attract the termite. These baits need to be moist because Coptotermes curvignathus’s body easier to dry out. The Seasonal climatic conditions which is wet season also can exert a strong influence on insect number and activity. The daytime in collecting the Coptotermes curvignathus which is during early morning is important due to its peak raiding activity. The number of termites that have been collected in PVC were killed by using Ridsect and the data were recorded. At the end of six weeks, the number of Coptotermes curvignathus decreased. Test of normality shown that the data is normally distributed (p > 0.05). The ANOVA Test was carried out, showing that there was significant difference in term of population number of Coptotermes curvignathus among the collection (p < 0.05).